Assessment of adaptation, policy, and capacity building outcomes from 14 processes. Issue 114 (December 2020) - Tuler, Seth P.; Dow, K.; Webler, T.
Highlights: We conducted an evaluation of fourteen implementations of a climate adaptation planning tool. Success of planning tools is a function of managing risks and of developing capabilities. Judgments about a process relate to development of capacities for planning and adaptation. Measuring success is a challenge when outcomes may be significant but not readily apparent in the short term. Abstract: In the US alone, there are over 200 tools that support climate adaptation planning, along with a large number of case studies documenting their use. Case studies frequently document positive results. Systematic assessment of processes can provide important benefits, including justification for action and expenditures, promotion of learning and adaptive management, accountability, and ensuring "fit" with other goals. There are very few such assessments in the context of climate adaptation planning, despite of the emphasis on the development and use of planning tools by federal and state agencies, university researchers, and non-profit organizations. We undertook an effort to assess the outcomes resulting from fourteen applications of the Vulnerability, Consequences, and Adaptation Planning Scenarios (VCAPS) process, which we helped develop and implement. VCAPS is designed to facilitate information exchange, co-production of knowledge, and stakeholder collaboration while helping communities appraise climate change-related risks and devise strategies to manage them. Using qualitative interviews we explored the perceived value and the measurable performance outcomes of VCAPS at both individual and community scales occurring 3–10 years after the processes were conducted, allowing participants to take a broader view of "success" and reflect on how different forms of success emerged over time. Although the assessment of each case is based on a small number of interviews, we learned that VCAPS informed plans and decisions of municipalities, informed actions and decisions of other public and private actors, generated broader support for subsequent actions, helped efforts to secure/seek funding for climate adaptation actions, developed material resources to support planning, and promoted learning among participants. This assessment also reinforces prior work showing that deliberative planning tools/processes are conducive to developing adaptive capacities; processes should be closely coordinated with regular governance activities to impact policy and action; adequate time for deliberation needs to be budgeted; participants need support to "think outside the box" and consider adaptation strategies that are both incremental and transformational as well as highlight potential undesirable consequences of adaptation; and processes, like VCAPS, produce actionable outcomes when participants agree on the immediacy of the issue. We conclude with observations about the need for evaluation of participatory processes and the challenges of defining success of tools to support municipal climate change adaptation planning.